SISTEM PENGINTEGRASI KONTEN SITUS JEJARING SOSIAL UNTUK PENCARIAN ORANG BERBASIS WEB SEMANTIK - , PRISA MARGA KUSUMANTARA; , Dr. techn. Khabib Mustofa, M.Kom ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The social network era has growing rapidly. Each social network site offers unique features. One user can have many accounts on different social networking causing unintegrated data problems. The search function on several social networks have limitations such as : the search is still text-based, static search criteria, as well as the output format still in textformat. ISIJASANTIK is an online friend finder system of integrated several social network sites based on dynamic multi context keyword. ISIJASANTIK developed by grabbing web, semantic web and web service approachs. Web grabbing techniques used to obtain and integrate the person's content metadata through social networking APIs. FOAF and GEO ontology has been modified and added a new context called \"shareKonteks\" which allowing users to share new context knowledge on nodes mutually relevant. Furthermore, the selection of AND and OR operators are flexible, supported interconnect with Google API is able to produce the information getting richer, informative and interactive.